Bargaining and Strikes - Hart, Oliver (Quarterly Journal of Economics, 1989)
A recent literature has shown that asymmetric information about a firm's profitability does not by itself explain strikes of substantial length if the firm and workers can bargain very frequently without commitment. In this paper we show that substantial strikes are possible if (a) there is a small (but not insignificant) delay between offers; and (b) a strike-bound firm may experience a decline in profitability after a certain point. A brief discussion of the ability of the theory to explain the data on strikes is included.